The Japanese Concept of Amae: New Light on Henri Nouwen’s Experience of Depression - Uemura, Kenjiro (Pastoral psychology, 2021)
This paper aims at showing that a renowned Catholic priest Henri Nouwen was suffering from strong unmet amae or the desire to be loved during his depressive experience. Through the Japanese unique concept of amae, new light is shed on Nouwen’s depression. First, the author explains the concept of amae, giving two examples from Western works. Second, he argues that Nouwen’s amae emotions can mainly be found in his work The Inner Voice of Love. Third, Nouwen’s famous concept of the ‘wounded healer’ is discussed in connection with training analysis, and it is contended that training analysis requires the analysand to confront the shadow aspects of their personality, one of which is negative amae emotion, such as childishness or immaturity. Fourth, it is contended that Nouwen’s depression played a part in his self-analysis. In overcoming his depression, Nouwen managed to come to terms with his amae and bodiliness. The article explores Nouwen’s depression from a holistic standpoint. In addition, the author argues that the concept of amae can help individuals understand their desire to be loved from the very early stage of infancy to adulthood.